The political economy of news in China : manufacturing harmony - Hearns-Branaman, Jesse Owen (Lexington Books, 2015)
Hearns-Branaman presents a full-scale application of Herman and Chomsky's propaganda model to the People's Republic of China, examining the effects of concentrated media ownership, profit motive, the influence of advertisers and flak-generating groups, sourcing patterns of media, and dominant ideology.